Red Kidney Bean Powder Substituted Milk in Cinnamon Herbal Coffee: Consumer Perception, Sensory Properties and Nutrition Content - Noor Ariefandie Febrianto; Khalimatus Sa'diyah; Tejasari Tejasari (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Consumer perspective of consuming coffee product has begun to shift not only for solely “pleasure” purpose, but also to consider its beneficial aspects. Red kidney bean (Phaseolus vulgaris L.) is a good source of fiber, protein and micronutrients to enhance the quality of beverages. This research was aimed to evaluate the effort to substitute milk with red bean powder in cinnamon herbal coffee and to study the enhancement of its nutrition content as well as the consumer perception and sensory properties. Red kidney bean powder was used to substitute milk powder and was blended with pre-mixed cinnamon coffee approximately 4%, 8%, 12%, 16% and 20% to obtain ready to drink mixtures. The coffee and control were then subjected to consumer perception to 25 panelists and sensory analysis by three trained-panelists and were also analyzed for its relation with nutrition content. The result showed that the substitution of milk with red kidney bean powder up to 8% could still be accepted by untrained panelist and its addition up to 20% still acceptable by trained-panelists. Addition of red bean powder could improve protein content up to 89.3% and 133.0% of soluble fiber content compared to the coffee that used full milk powder. This result showed that red kidney bean powder could be used to substitute milk powder in coffee beverages since it significantly improved the nutrition value and resulted in good sensory properties.